2017
DOI: 10.2140/gt.2017.21.1131
|View full text |Cite
|
Sign up to set email alerts
|

Outer space for untwisted automorphisms of right-angled Artin groups

Abstract: For a right-angled Artin group A Γ , the untwisted outer automorphism group U(A Γ ) is the subgroup of Out(A Γ ) generated by all of the Laurence-Servatius generators except twists (where a twist is an automorphisms of the form v → vw with vw = wv). We define a space Σ Γ on which U(A Γ ) acts properly and prove that Σ Γ is contractible, providing a geometric model for U(A Γ ) and its subgroups. We also propose a geometric model for all of Out(A Γ ) defined by allowing more general markings and metrics on point… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
105
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(105 citation statements)
references
References 16 publications
0
105
0
Order By: Relevance
“…The untwisted subgroup U (A Γ ) of Out(A Γ ) is defined to be the subgroup generated by So U (A Γ ) is generated by the Laurence generating set with the adjacent transvections taken out. Charney-Stambaugh-Vogtmann [11] have shown that U (A Γ ) has a proper action on a space, called an outer space for A Γ . Let U 0 (A Γ ) be the intersection of the untwisted subgroup with Out 0 (A Γ ).…”
Section: Previously Studied Relative Automorphism Groupsmentioning
confidence: 99%
“…The untwisted subgroup U (A Γ ) of Out(A Γ ) is defined to be the subgroup generated by So U (A Γ ) is generated by the Laurence generating set with the adjacent transvections taken out. Charney-Stambaugh-Vogtmann [11] have shown that U (A Γ ) has a proper action on a space, called an outer space for A Γ . Let U 0 (A Γ ) be the intersection of the untwisted subgroup with Out 0 (A Γ ).…”
Section: Previously Studied Relative Automorphism Groupsmentioning
confidence: 99%
“…Some of the terminology has been altered slightly, and we will point this out when it occurs. We refer to [5] for more details and all proofs. 3.1.…”
Section: 2mentioning
confidence: 99%
“…For the subgroup U (A Γ ) associated to a general RAAG, an analogous outer space O Γ and spine K Γ were defined in [5]. The dimension of K Γ gives an obvious upper bound on the vcd of U (A Γ ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The group normalU0false(AΓfalse)< Out false(AΓfalse) is the intersection of the group U(AnormalΓ) of untwisted outer automorphisms (introduced by Charney–Stambaugh–Vogtmann ) with the finite index subgroup Out 0false(AΓfalse).…”
Section: Introductionmentioning
confidence: 99%